Adopting proactive results by developing the Shrewd model of pandemic COVID-19 - Shahzad Ashraf; Zeeshan Rasheed; Muhammad Arbaz (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
The unavoidable pandemic situation seems uncontrolled over the past two years. In this aggravated situation, it seems crucial to take inescapable measures to deal with such a defiant disease and it is only possible if the actual pandemic propagation ratio is to be acquainted. Therefore, a shrewd pandemic model is being developed that will generate real-time infection statistics on an hourly, weekly, and monthly basis. This shrewd model utilizes the well-known dataset and when this dataset will be applied to determine the status of three types of infection the number of infected people, the time when the pandemic begins, and the time when the pandemic disappears. The time-based results are generated by conducting simulation in python Simpy framework and the generated results are the hallmark of real-time infection spreading ratio it shows that when the extraordinary measures for infection ratio are indispensable and when it becomes plausible.